Genomic and Phenotypic Characterization of Cutibacterium acnes Bacteriophages Isolated from Acne Patients - Shukho Kim; Hyesoon Song; Jong Sook Jin; Weon Ju Lee; Jungmin Kim (MDPI AG, 2022)
Cutibacterium acnes is a pathogen that can cause acne vulgaris, sarcoidosis, endodontic lesions, eye infections, prosthetic joint infections, and prostate cancer. Recently, bacteriophage (phage) therapy has been developed as an alternative to antibiotics. In this study, we attempted to isolate 15 phages specific to C. acnes from 64 clinical samples obtained from patients with acne vulgaris. Furthermore, we sequenced the genomes of these three phages. Bioinformatic analysis revealed that the capsid and tape measure proteins are strongly hydrophobic. To efficiently solubilize the phage particles, we measured the adsorption rate, one-step growth curve, and phage stability using an SMT2 buffer containing Tween 20. Here, we report the genotypic and phenotypic characteristics of the novel C. acnes-specific phages.